Radio-frequency connectors. Sectional specification. RF coaxial connectors with inner diameter of outer conductor 4, 13 mm (0, 163 in) with threaded coupling. Characteristic impedance 50 Ω (type SMA) Part 15, (4th March 2021) - British Standards Institution,
No abstract available